EPEN-01. C11ORF95-RELA DICTATES ONCOGENIC TRANSCRIPTIONAL PROGRAMS TO DRIVE AGGRESSIVE SUPRATENTORIAL EPENDYMOMA. (1st June 2021) - Arabzade, Amir; Zhao, Yanhua; Varadharajan, Srinidhi; Chen, Hsiao-Chi; Bertrand, Kelsey; Deneen, Benjamin; Mack, Stephen
Abstract: Over 60% of supratentorial (ST) ependymomas harbor a gene fusion between C11orf95, an uncharacterized gene, and RELA (also known as p65), a main component of the NF-ĸB family of transcription factors. While its sufficiency to drive tumor has been established, the mechanism of tumorigenesis remains elusive. To tackle this question, we developed a natively forming mouse tumor model using in utero electroporation (IUE) of the embryonic mouse brain and performed integrative epigenomic and transcriptomic mapping. Our findings indicate that in addition to direct canonical NF-ĸB pathway activation, C11 orf 95- RELA (CR fus ) dictates a neoplastic transcriptional program and binds to unique sites across the genome enriched with Plagl family transcription factor motifs. CR fus modulates the transcriptional landscape by recruiting transcription co-activators (Brd4, EP300, Cbp, Pol2) which are amenable to pharmacologic inhibition. Downstream CR fus target genes converge on developmental programs marked by Plagl family of transcription factors and activate neoplastic programs enriched in Mapk, focal adhesion, and gene imprinting networks, many of which contain previously unreported therapeutic leads in C11 orf 95- RELA ependymoma.